EVALUATION OF THE EFFICACY OF CARDAMOM AROMATHERAPY ON AEROBIC FITNESS & AUTONOMIC FUNCTIONS AMONG STUDENTS. - Patil, Shrikant L.; Sreekumaran, E.; Krishna, A.P. (Journal of Health and Allied Sciences NU, 2011)
Introduction: Aromatherapy is categorized as a form of complementary and alternative medicine (CAM), and has been steadily gaining popularity in today's society. Aromatherapy is considered by many to promote comfort, well-being and invigorating. However there appears to be insufficient supporting evidence to validate physiological changes that may reflect invigoration.Objectives: This study examined the physiological effects of cardamom (Elettaria cardamomum) aromatherapy as indicated by heart rate variability. Aerobic fitness is one of the non invasive and simplest parameters which help in accessing one's fitness. In this present study we have also evaluated the efficacy of aromatherapy on the individual's physical fitness.Methods: Total thirty healthy college students were selected as a subject who has attended four sessions in random order involving only exercise, aromatherapy and exercise combined. Each intervention lasted 15 minutes. Heart rate data were recorded for all sessions, and heart rate variability was analyzed. Aerobic fitness parameters also evaluated with the help of standard methods.Results: There was statistically significant difference in LF/HF between the two intervention studies. During this aromatherapy, physiological responses such as oxygen consumption, respiratory exchange ratio and minute ventilation were significantly altered among different groups. Aerobic fitness was observed higher in aromatherapy combined exercise group against the only exercise group.Conclusion: These results suggest significant physiological effect of cardamom (Elettaria cardamomum) aromatherapy interventions occurs in the autonomic nervous system as indicated by heart rate variability. The present study demonstrates that good estimated aerobic fitness was independently associated with aromatherapy and exercise.
Keywords: Aromatherapy; autonomic function; aerobic fitness; exercise